1989
DOI: 10.1029/wr025i010p02109
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of solute transport during transient irrigation: 1. The effect of hysteresis and profile heterogeneity

Abstract: Most of the existing data on vadose zone field scale solute transport have been obtained from experiments conducted under transient, nonmonotonic water flow. However, the majority of the theoretical analyses of these experiments have used models which assume monotonic steady state water flow and uniform water content for the entire profile. In this study, transport of nonreactive solutes under nonmonotonic, transient water flow is analyzed numerically. The effect of hysteresis on solute transport is evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 31 publications
(29 reference statements)
1
33
0
4
Order By: Relevance
“…This is because when hysteresis is included in the flow analysis, the relative large change in matrix potential head on reversal from wetting to drying produces only a small change in water content compared to the change predicted from a single wetting Q(H) curve. This is in agreement with results presented by Russo et al (1989) who simulated one-dimension infiltration without considering root-water uptake and evaporation from the soil surface. Figures 3(a, b) to 6(a, b) also show that when hysteresis is neglected and the wetting Q(H) curve is used for both wetting and draining, on reversal the draining process will be much more rapid than with hysteresis included.…”
Section: Results and Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…This is because when hysteresis is included in the flow analysis, the relative large change in matrix potential head on reversal from wetting to drying produces only a small change in water content compared to the change predicted from a single wetting Q(H) curve. This is in agreement with results presented by Russo et al (1989) who simulated one-dimension infiltration without considering root-water uptake and evaporation from the soil surface. Figures 3(a, b) to 6(a, b) also show that when hysteresis is neglected and the wetting Q(H) curve is used for both wetting and draining, on reversal the draining process will be much more rapid than with hysteresis included.…”
Section: Results and Analysissupporting
confidence: 93%
“…Hysteresis can significantly influence water flow in variably saturated porous media (Vachaud and Thony, 1971;Gillham et al, 1979;Russo et al, 1989). Hysteresis refers to the non-unique relationship between the pressure head, H, and the water content, Q, in the soil water characteristic curve (SWCC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various hypotheses have been invoked to explain possible factors that affect the migration and distribution of solutes under unsaturated, heterogeneous conditions, including turbulent mixing due to high rainfall (Havis et al, 1992); solute transfer between mobile and immobile water (De Smedt and Wierenga, 1984); mobile-immobile exchange and hysteresis (Butters et al, 1989;Russo et al, 1989aRusso et al, , b, 2014; lateral mixing due to velocity fluctuations (Russo et al, 1998); isotope effects (Barnes and Allison, 1988;LaBolle et al, 2008;Zhang et al, 2009);variable, state-dependent anisotropy (McCord et al, 1991); non-Gaussian early-time mean tracer plume behavior (Naff, 1990); non-Fickian solute migration at low water contents (Padilla et al, 1999) and for macroscopically homogeneous sand (Bromly and Hinz, 2004); and saturation-dependent dispersivity (Raoof and Hassanizadeh, 2013). In addition, Konikow et al (1997) and Parker and van Genuchten (1984) discuss the importance of boundary condition treatment (e.g., water-solute injection, solute exchange between soil and atmosphere).…”
Section: Discussionmentioning
confidence: 99%
“…Neglecting hysteresis leads to significant errors in the water redistribution under transient boundary conditions (Dane and Wierenga, 1975;Gillham et al, 1979, Hoa et al, 1977Viaene et al, 1994;Lehmann et al, 1999;Si and Kachanoski, 2000). Russo et al (1989) and Mitchell and Mayer (1998) investigated the influence of hysteresis on solute transport and found that the magnitude of the deviations between hysteretic and nonhysteretic simulations was not a simple function of single parameters, but rather depended on the combined values of many or all of the hydraulic parameters. Hysteresis is also seen as one of the major obstacles for comparing different measurement methods for the K(θ ) (Stolte et al, 1994;Basile et al, 2003).…”
Section: Hysteresismentioning
confidence: 99%